1979
DOI: 10.3758/bf03209272
|View full text |Cite
|
Sign up to set email alerts
|

Stimulus control of behavior during the postreinforcement pause of FI schedules

Abstract: Pigeons were given the opportunity to terminate certain segments of fixed intervals by pecking a control key. When 3D-sec segments of negative and positive stimuli alternated across the interreinforcement interval (Experiment 1), most birds terminated a large proportion of negative segments. However, few control-key responses were made during the negative segment immediately following food presentation. Under schedules during which only one negative segment was programmed, during the first 30 sec of 1-min inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
6
0

Year Published

1981
1981
2000
2000

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 19 publications
3
6
0
Order By: Relevance
“…In general, there was a burst of attack following a food delivery regardless of whether or not food signaled a period of no food, although in Experiment II the rate of postfood attack for the RT group was less than for the FT group. This postfood burst of attack is consistent with suggestions that there are aftereffects of reinforcement (Innis & Honig, 1979;Solomon & Corbit, 1974) and that schedule-induced attack is induced by interrupted access to or the withdrawal of a reinforcer (e.g., Azrin et al, 1966;Hutchinson, 1973). The present results also support the idea that schedule-induced behavior may reflect the elicitation of arousal by the reinforcer (Killeen, 1975).…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…In general, there was a burst of attack following a food delivery regardless of whether or not food signaled a period of no food, although in Experiment II the rate of postfood attack for the RT group was less than for the FT group. This postfood burst of attack is consistent with suggestions that there are aftereffects of reinforcement (Innis & Honig, 1979;Solomon & Corbit, 1974) and that schedule-induced attack is induced by interrupted access to or the withdrawal of a reinforcer (e.g., Azrin et al, 1966;Hutchinson, 1973). The present results also support the idea that schedule-induced behavior may reflect the elicitation of arousal by the reinforcer (Killeen, 1975).…”
Section: Discussionsupporting
confidence: 88%
“…The induction of postreinforcement attack by inter-101 1981, 36., [101][102][103][104][105][106][107][108][109][110][111][112][113][114][115][116][117] mittent reinforcement alone would be consistent with suggestions by Azrin et al (1966), Hutchinson (1973), and others (Gentry, 1968;Rilling, 1977;Rilling & Caplan, 1975) that the termination or withdrawal of a reinforcer induces aggression. This view is compatible with the proposal that there are aftereffects of reinforcers (Innis & Honig, 1979;Solomon & Corbit, 1974) and that schedule-induced behavior, including attack, may reflect motivational sequelae of reinforcers (Killeen, 1975). Millenson, Allen, and Pinker (1977) and Lashley and Rosellini (1980) have examined this question with regard to schedule-induced polydipsia in rats and have found that constant-probability food schedules were effective in inducing polydipsia in fewer rats than schedules with variations in reinforcer probability.…”
supporting
confidence: 65%
“…We used the same general procedure as before; differences included a third procedure, the clamped condition, for which food delay, T, was complementary to waiting time, t: t + T = C, a constant, so that interfood interval was independent of t for all t < C (this procedure resembles what has been called a conjunctive fixed-ratio 1, fixed-time schedule: Shull, 1970;Staddon & Frank, 1975; see also Innis & Honig, 1979). Also, conditions were changed daily, rather than remaining constant across several days.…”
Section: Versus Food Delay With Fixed Dependent and Clamped Delaysmentioning
confidence: 99%
“…They have noted that during the postreinforcement pause following response-contingent food reinforcement, pigeons are unlikely to engage in pecking behavior that initiates a fixed-interval period (Shull, 1970), terminates a reinforcement schedule (Brown & Flory, 1972), or increases reinforcement rate. Although the results of this experiment cannot account for the post-reinforcement inhibition of keypecking, they do rule out the hypothesis (Innis & Honig, 1979) that, following food reinforcement, pecks that topographically resemble feeding behavior are inhibited. This is not the case, since vigorous feeding-like pecks readily occur immediately following food reinforcement when those pecks are directed toward the head of a conspecific target located away from the reinforcer dispenser.…”
Section: Resultsmentioning
confidence: 59%
“…Results obtained with food-reinforced subjects bear on another issue raised by Innis and Honig (1979). They have noted that during the postreinforcement pause following response-contingent food reinforcement, pigeons are unlikely to engage in pecking behavior that initiates a fixed-interval period (Shull, 1970), terminates a reinforcement schedule (Brown & Flory, 1972), or increases reinforcement rate.…”
Section: Resultsmentioning
confidence: 94%